Water Stable Haloplumbate Modulation for Efficient and Stable Hybrid Perovskite Photovoltaics. Issue 25 (16th May 2021) - Wang, Huanhuan; Zhang, Zhuang; Milić, Jovana V.; Tan, Liguo; Wang, Zaiwei; Chen, Rong; Jing, Xin; Yi, Chenyi; Ding, Yi; Li, Yuelong; Zhao, Ying; Zhang, Xiaodan; et al.
Abstract: The commercialization of perovskite solar cells is mainly limited by their operational stability. Interlayer modification by thin interface materials between the perovskite and the charge transport layers is one of the most effective methods to promote the efficiency and stability of perovskite devices. However, the commonly used interlayer materials do not fulfill all the demands, including good film quality, excellent stability, and passivation capability without interfering with the charge transport. In this work, a water stable haloplumbate [TBA]PbI3 for interfacial modification that meets these demands is proposed, which is formed on the perovskite surface in situ by tetra ‐butylammonium iodide treatment. Benefiting from its passivation effect and robustness, the modified devices result in a power conversion efficiency of 22.90% with enhanced environmental and operational stability. In addition, the self‐limiting effect of the reaction contributes to the controllability of device fabrication and the repeatability of device performance. Abstract : Interfacial engineering of thin interlayers on the surface of a perovskite is shown to be one of the most effective methods for improving the stability of perovskite solar cell (PSCs). Here, a water stable haloplumbate for modulation of PSCs is introduced, which shows an protective effect against water and improves the power conversion efficiency and stability of perovskite solar cells.